Aplikasi Pencarian dan Pembelajaran Hadist Pada Kitab Riyadhus Shalihin Berbasis Mobile - Anik Sri Wahyuningsih; Dudi Nurdiana (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2016)
Hadith is one way of life of Muslims after the Qur'an. Law - Islamic law regulated in the hadith as a law that strengthens the holy verses of the Qur'an. In the hadith contains sayings of the Prophet are then recorded, so many Muslims who are looking for basic - the legal basis based on the hadith is used as a legal basis. To petrified and support the learning we need a system that can search hadith application in accordance with the needs of knowledge, basic law and learning. The purpose of the study authors is to build a search system and hadith with mobile-based learning. It is expected that the application is made the author a reference to improve the deeds of Muslims and ketaqwaanya hello to Allah